2021
DOI: 10.1152/ajpgi.00061.2021
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D/VDR signaling inhibits colitis by suppressing HIF-1α activation in colonic epithelial cells

Abstract: Vitamin D/vitamin D receptor (VDR) signaling is reported to have a protective effect on the onset or progression of inflammatory bowel diseases (IBD) and hypoxia-inducible factor 1α (HIF-1α) activation is demonstrated to be closely associated with chemical-induced colitis. However, the association between vitamin D/VDR signaling and HIF-1α on IBD development remains a mystery. Here, we showed that HIF-1α expression was largely increased in the colonic epithelial cells of diseased tissues from ulcerative coliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Multiple studies included in this study showed that vitamin D supplementation effectively reduced the levels of inflammatory factors (IL-6, TNF- α , and CRP) in patients with ulcerative colitis. The proposed inflammatory outcome index was consistent with Xue et al [ 27 ]. Xue et al collected biopsy samples from 103 patients with UC and found that vitamin D/vitamin D receptor (VDR) signaling has a protective effect on the onset or progression of inflammatory bowel disease (IBD) and proved that the activation of hypoxia-inducible factor 1 α (HIF-1 α ) is closely related to inflammatory factors.…”
Section: Discussionsupporting
confidence: 87%
“…Multiple studies included in this study showed that vitamin D supplementation effectively reduced the levels of inflammatory factors (IL-6, TNF- α , and CRP) in patients with ulcerative colitis. The proposed inflammatory outcome index was consistent with Xue et al [ 27 ]. Xue et al collected biopsy samples from 103 patients with UC and found that vitamin D/vitamin D receptor (VDR) signaling has a protective effect on the onset or progression of inflammatory bowel disease (IBD) and proved that the activation of hypoxia-inducible factor 1 α (HIF-1 α ) is closely related to inflammatory factors.…”
Section: Discussionsupporting
confidence: 87%
“…Three distinct HIF isoforms exist in mammals, of which HIF1A (Hypoxia Inducible Factor 1 Subunit Alpha) is commonly expressed ( Wang and Semenza, 1993 ). Vitamin D/VDR signaling suppresses UC by inhibiting the activation of HIF-1α in colonic epithelial cells ( Xue et al, 2021 ). Qi Lv et al have shown that the suppression of HIF-1α-mediated glycolysis by costunolide acts specifically in the differentiation of Th17 cells and consequent UC relief, and it also provides a novel prospective for the immunometabolic treatment of colitis ( Lv et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…KLF5 has been reported to regulate intestinal epithelial cell proliferation ( 32 ), particularly in the context of colon cancer ( 33 ). HIF1A has been reported to accelerate inflammatory responses ( 34 ) and 1,25(OH) 2 D 3 signaling has recently been proposed by others to inhibit colitis by inhibiting HIF1A activation in colonic epithelial cells ( 35 ).…”
Section: Discussionmentioning
confidence: 99%